2021
DOI: 10.3389/fphar.2021.707687
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Phytochemical Analysis Based on UPLC–MS/MS and Network Pharmacology Approaches to Explore the Effect of Odontites vulgaris Moench on Rheumatoid Arthritis

Abstract: Odontites vulgaris Moench has the effect of clearing away heat, detoxification, dispelling wind, and clearing dampness. In this study, the potential anti-inflammatory compounds of O. vulgaris were investigated using ultra-high-performance liquid chromatography–mass spectrometry (UPLC–MS/MS) combined with the network pharmacology approach and further confirmed on an LPS-activated RAW 264.7 macrophage model. Monomer compounds were prepared from the active fraction using modern advanced separation and purificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…[41], respectively. In the recent literature, it has been reported that compound 4 has anti-inflammatory activity [42], along with other iridoids not reported herein, which linked to a study on the potential activity of Odontites vulgaris against rheumatoid arthritis. In an even earlier study [43] including other iridoids and compound 4, the latter was also found to be cardioactive in Wistar rats.…”
Section: Resultsmentioning
confidence: 62%
“…[41], respectively. In the recent literature, it has been reported that compound 4 has anti-inflammatory activity [42], along with other iridoids not reported herein, which linked to a study on the potential activity of Odontites vulgaris against rheumatoid arthritis. In an even earlier study [43] including other iridoids and compound 4, the latter was also found to be cardioactive in Wistar rats.…”
Section: Resultsmentioning
confidence: 62%
“…The main compositions of Khurtsiin Deed-6 traditional medicine are Odontites Vulgaris Moench and Carthamus tinctorius L, and they contain apigenin, flavonol-O-glycoside (hyperoside, isoquercetin), flavonoids (quercetin, kaempferol, rutin) and Carthamus tintorius L. also contains hydroxysafflor yellow A. 4,24,25 The rhizome of Saussurea lappa L. contains biologically active compounds such as sesquiterpene, costunolide, and dihydrocostulactone. 26 Some study results of Saussurea lappa L. showed that costunolide can be an inhibitor of NO, iNOS, and TNF-a.…”
Section: Discussionmentioning
confidence: 99%
“…The compounds are mainly divided into four categories: phenylethanoid glycosides (verbascoside, isoacteoside, arenarioside, salidroside), flavonoids (kaempferol, cynaroside, luteolin, luteolin-7-O-glucuronide, apigenin, apigenin-7-O-glucoside, tricin, chrysoeriol, quercetin, diosmetin, hydroxygenkwanin), iridoids (melampyroside, shanzhiside methyl ester, aucubin, geniposide, geniposidic acid, shanzhiside methyl ester), phenolic acids (caffeic acid, trans-cinnamic acid, 2-hydroxycinnamic acid, salicylic acid, ferulic acid, 7,8-dihydroxycoumarin) and others (adenosine, syringaresinol, D-Mannitol, esculetin). 4 Numerous researches conducted on T.chebula have confirmed the presence of wide range of the phytochemicals such as flavonoids, tannins, phenolic acids and other bioactive compounds. Juang et al (2004) developed an reverse-phase HPLC method for the determination of 14 phenolic components of hydrolyzable tannins (gallic acid, chebulic acid, chebulanin, corilagin, punicalagin, neochebulinic acid, ellagic acid, chebulegic acid, chebulinic acid,1,2,3,4,6-Penta-O-galloyl-β-D-glucose, 1,6,-di-O-galloyl-D-glucose, casuarinin, 3,4,6-tri-O-galloyl-D-glucose, terchebulin) in the fruits of T.chebula.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, a binding energy of ≤ 5.0 kcal/mol indicates a good binding effect. PyMol 2.3.2 software was used for visualization ( 15 ).…”
Section: Methodsmentioning
confidence: 99%